Quilt with Tula & Angela : A Start-to-FinishGuide to Piecing and Quilting Using Color and Shape - Pink, Tula; Walters, Angela; 1979- (Blue Ash, Ohio, 2016)
Known for her cool, innovative style, Tula Pink will inspire you to toss your mundane color wheel and commit to her signature approach. Angela Walters creates the complementary finish and surface texture for each design, resulting in the perfect marriage of color and style for each of the featured 17 quilt projects.
Keywords: Quilting; Patterns; Patchwork; Patterns